2012
DOI: 10.1371/journal.pone.0050461
|View full text |Cite
|
Sign up to set email alerts
|

RAD52 Variants Predict Platinum Resistance and Prognosis of Cervical Cancer

Abstract: RAD52 is an important but not well characterized homologous recombination repair gene that can bind to single-stranded DNA ends and mediate the DNA-DNA interaction necessary for the annealing of complementary DNA strands. To evaluate the role of RAD52 variants in the response of tumor cells to platinum agents, we investigated their associations with platinum resistance and prognosis in cervical cancer patients. We enrolled 154 patients with cervical squamous cell carcinoma, who had radical surgery between 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
18
2
Order By: Relevance
“…Immunohistochemistry (IHC) assay. The 10x12 (120 cores) tissue microarray (TMA) was made by FUSCC Tissue Bank, as described previously (15). Each case has two cores made from separate sources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry (IHC) assay. The 10x12 (120 cores) tissue microarray (TMA) was made by FUSCC Tissue Bank, as described previously (15). Each case has two cores made from separate sources.…”
Section: Methodsmentioning
confidence: 99%
“…We used the 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-diphenytetrazoliumromide (MTT) assay to detect in vitro inhibition rates of four platinum agents (cisplatin, carboplatin, nedaplatin and oxaliplatin), as described previously (15). Optical densities (OD 570 nm ) were measured by Microplate Reader (Bio-Rad 550; Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Plasmid Construction and Cell Transfectionmentioning
confidence: 99%
“…Previous studies have shown that therapy response can vary significantly among patients due to interindividual variations of DNA repair activity caused by the presence of genetic alterations in DNA repair genes which results in DNA repair deficiency and hence with chemoradiotherapy sensitization (Nogueira et al, 2012, de las Penas et al, 2006, Shi et al, 2012, Chung et al, 2006. Because of the importance of this process in determining sensitivity and resistance, components of the DNA damage repair pathways have been studied with regard to genetic variation and response to therapy (Hildebrandt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was speculated that low non-physiological levels of RAD52 could promote a dysregulated HDR and this could possibly up-regulate error-prone backup repair pathways. Another study [63] has found that low RAD52 expression is associated with a poor response of cervical cancer cells to carboplatin. It was suggested that RAD52 SNPs, either individually or collectively, could modify gene function and alter RAD52 protein expression levels, making the cervical cancer cell resistant to platinum agents.…”
Section: Discussionmentioning
confidence: 98%